2016
DOI: 10.5114/ada.2016.62838
|View full text |Cite
|
Sign up to set email alerts
|

Are interleukin-15 and -22 a new pathogenic factor in pustular palmoplantar psoriasis?

Abstract: IntroductionPustular palmoplantar psoriasis (PPP) is a rare type of psoriasis affecting mainly distal parts of the limbs. Despite numerous theories about etiology of PPP, the pathogenesis still remains unclear. Recent data indicate that interleukin (IL)-15, IL-17 and IL-22 enhance a proinflammatory response in certain skin inflammatory diseases such as psoriasis and atopic dermatitis. There is also evidence that anti-endomysial (anti-EMA) and anti-gliadin (AGA) antibodies are engaged in PPP development.AimTo a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Swedish studies have shown a high prevalence of antigliadin and anti-tissue transglutaminase antibodies, coeliac disease, and disturbed calcium homeostasis in patients with PPP [3,6,28]. However, a study in German and Polish populations did not confirm these observations, and these laboratory tests are not routinely performed in patients with PPP in our clinical practice [7,29,30].…”
Section: Coeliac Diseasementioning
confidence: 98%
See 2 more Smart Citations
“…Swedish studies have shown a high prevalence of antigliadin and anti-tissue transglutaminase antibodies, coeliac disease, and disturbed calcium homeostasis in patients with PPP [3,6,28]. However, a study in German and Polish populations did not confirm these observations, and these laboratory tests are not routinely performed in patients with PPP in our clinical practice [7,29,30].…”
Section: Coeliac Diseasementioning
confidence: 98%
“…Lesiak et al [29] found elevated levels of IL-15 and IL-22 in the sera of female patients with PPP. We know that IL-15 induces IL-17 production and IL-22 enhances the proinflammatory action of IL-17 [29].…”
Section: Interleukin (Il)-17 Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Its expression in acute atopic dermatitis is decreased,[17] whereas it is highly expressed in psoriatic plaques[18] and in pustular palmoplantar psoriasis. [19]…”
Section: Discussionmentioning
confidence: 99%
“…IL-15 has similar biological effects as IL-2, however, distinct key roles were identified during development and function of CD8+ T cells, natural killer cells, invariant natural killer-T cells, and intestinal intraepithelial lymphocytes (Castillo and Schluns, 2012). High serum levels of IL-15 were implicated in the pathogenesis of pustular palmoplantar psoriasis (Lesiak et al, 2016), which is an infrequent type of psoriasis disturbing primarily distal parts of the limbs. Likewise, higher levels of IL-15 were correlated with the activity of NK cells in the pathogenesis of psoriatic arthritis (Tang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%